The Food Insecurity Issues in Gastronomy Tourism among Local and International Tourists in Malaysia - Ismail, Nazrul Hadi; Zulfa, Nur Quratul Aini; Muhammad Ramly, Alina Shuhaida; Md Sharif, Mohd Shazali; Md Nor, Norazmir (Jurnal Gizi dan Pangan, 2024)
The objectives of this study are to investigate the food security issues arising in gastronomic tourism, to verify the food insecurity experiences encountered by tourists, and to determine the tourists’ dining satisfaction from the gastronomic tourism experiences in Malaysia. A quantitative approach was selected for this study. These issues were concluded from the data collection via questionnaire forms disseminated online through multiple social media platforms consisting of 250 participants of both local and international tourists visiting Malaysia. The Independent T-test and Mann-Whitney test were used as the main statistical test to establish if any tourist groups had food security-related issues during their visit. The results showed that local tourists are more likely to be affected by food security issues, food insecurity, and dining experiences. Overall, this study discovered that both local and international tourists have contrasting experiences in gastronomy tourism in Malaysia.